Possession and the Senses in Early Modern England - Gasser, Erika (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
This article addresses the history of possession and preternatural interference through the lens of the senses. Because these sorts of cases featured the intersection of embodied and ephemeral perception, they provide singular opportunities to evaluate elite and popular conceptions of humans’ capacity to sense what lay within and beyond the natural realm. Possession cases also offer a prime opportunity to examine how attempts to ascribe meaning to bodily acts required that writers present the senses of afflicted individuals and those who attended them as intricately connected. Published possession texts thus provide an entry point from which to evaluate aspects of “intersensorality,” when witnesses appeared both to experience overlapping senses themselves and occasionally to find their perceptions linked with afflicted persons in ways that surpassed what was natural. The paper also examines the role that insensibility played in some instances of possession propaganda, both when subjects experienced complete trances and when they displayed selective inability to see, hear, or speak in reaction to cultural cues.